Studi Komersialisasi Benih Padi Sawah Varietas Unggul - Setia Hadi; Tati Budiarti; , Haryadi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2005)
Rice is the most important food in Indonesia and the rice demand has gradually increased during some decades.  There are several efforts to increase national rice production in order to minimize  rice import, such as using seed of improved variety, fertilizer, protection from pest and diseases, improving water management  and post harvest handling.  Cultivation of improved  variety is the most efficient way to  increase  rice production in Indonesia.   There are several improving characteristics on new released variety such as : early mature, high productivity, resistant to pests and diseases, resistant to lodging, and  high quality of rice.  During 1960 - 2000, more than 90 improved varieties were released by Ministry of Agriculture, but only several varieties (about 10%)  were accepted by the farmer and  cultivated in a large-scale area during  a long periode.   IR 64 is the most popular variety in many provinces more than 12 years, so that the variety has the  highest commercial level  and  efficency index among Cisadane, PB 42, PB 46 and the old improved variety.    Key words: Rice, Commercialization, Efficiency index